17β-estradiol promotes osteogenic differentiation of BMSCs by regulating mitophagy through ARC - Jingcun Shi; Jin Wen; Longwei Hu (Journal of Orthopaedic Surgery and Research, 2025)
Abstract The study aims to elucidate the mechanism through which 17β-estradiol facilitates osteogenic differentiation in bone marrow mesenchymal stem cells (BMSCs). In our study, lentiviral transfection was employed to establish apoptosis repressor with caspase recruitment domain (ARC) knockdown or overexpression in BMSCs. The impact of 17β-estradiol on ARC expression was assessed using western blot, RT-PCR and immunofluorescence. Techniques such as ALP staining, ALP activity assay, western blot, RT-PCR and immunofluorescence staining were utilized to examine the influence of ARC expression levels on the osteogenic differentiation of BMSCs and the osteoclastic differentiation of Raw264.7 cell lines. Mitophagy flux levels in BMSCs were detected using the mitophagy detection kit. RNA sequencing and bioinformatics analyses were conducted to explore potential mechanisms of ARC regulation in BMSCs osteogenic differentiation. To sum up, 17β-estradiol can modulate bone homeostasis by adjusting ARC expression. ARC stimulates mitophagy in BMSCs via MAPK/Akt pathway, identifying ARC as a promising therapeutic target for postmenopausal osteoporosis (PMOP) treatment.